Pengaruh Motivasi, Pengetahuan Kewirausahaan, dan Ekspetasi Pendapatan Terhadap Minat Berwirausaha Generasi Muda di Sektor Agrowisata - Nasution, Ade Iskandar; Mu'minin, Ayi Mi'razul; Nur'aeni, Nur'aeni (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The agricultural sector needs to be given attractive added value so that the younger generation does not leave it. One alternative is to combine the agricultural and tourism sectors into agrotourism. Agrotourism provides added value for farmers while still producing production crops and earning additional income from tourist visits. Agrotourism not only improves the standard of living of farmers but also facilitates market accessibility, thus attracting the attention of various parties. Thus, there needs to be an encouragement to make the younger generation interested in entrepreneurship in the agrotourism sector. The purpose of this study is to examine the influence of motivation, entrepreneurial knowledge, and income expectations on the entrepreneurial interest of the younger generation in the agrotourism sector. The research was conducted directly in the field, namely on the object of research in Cibodas Village, Lembang District, West Bandung Regency. Research data in the form of primary data obtained from respondents, namely young people living in the area. Data analysis is done through hypothesis testing in structural equation modeling (SEM) with the help of WarpPLS application.